2001
DOI: 10.1177/147323000102900413
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect of Etidronate on Alveolar Pyorrhoea Associated with Chronic Marginal Periodontitis: Report of Four Cases

Abstract: Etidronate 200 mg daily was administered to four female patients with periodontitis and resultant alveolar pyorrhoea for periods of 2 weeks, followed by off-periods of 10 weeks or more, for 2-3 years. The macroscopic appearance of gingival mobility of the teeth, depth of periodontal pockets, and X-ray findings of alveolar bones improved markedly during this time. The effects were first observed after 6-12 months of treatment. These findings indicate that bisphosphonates may be effective in the treatment of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Some patients in our study took risedronate or alendronate, which are bisphosphonates, which may improve periodontal health but also may cause osteonecrosis and painful refractory bone exposures of the jaws. 26-31 The incidence of osteonecrosis of the jaw in patients taking oral bisphosphonate therapy for osteoporosis is low, with a reported risk of less than 1 in 100,000 patients. 32 Some of the patients in our study took estrogen, which may benefit periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients in our study took risedronate or alendronate, which are bisphosphonates, which may improve periodontal health but also may cause osteonecrosis and painful refractory bone exposures of the jaws. 26-31 The incidence of osteonecrosis of the jaw in patients taking oral bisphosphonate therapy for osteoporosis is low, with a reported risk of less than 1 in 100,000 patients. 32 Some of the patients in our study took estrogen, which may benefit periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the effects of intermittent cyclical etidronate (ICE) administered to four patients with periodontal disease for 2 -3 years in addition to ordinary dental treatment for periodontitis. 1 This present study describes the results of following these same patients for an additional 2 -3 years.…”
Section: Introductionmentioning
confidence: 87%
“…Similarly, the level of NTX ⁄ creatine, a marker for bone resorption, had statistically significantly improved in the alendronate group at the end of the study. The case series reported by Takaishi et al (149) indicated that there was a clinical and radiographic improvement when a bisphosphonate was combined with conventional periodontal treatment.…”
Section: Role Of Bone-sparing Agentsmentioning
confidence: 99%
“…The case series reported by Takaishi et al. (149) indicated that there was a clinical and radiographic improvement when a bisphosphonate was combined with conventional periodontal treatment.…”
Section: Periodontal Management Of Osteopenia Patientsmentioning
confidence: 99%